2015
DOI: 10.17557/.51440
|View full text |Cite
|
Sign up to set email alerts
|

Spad Greenness to Estimate Genotypic Variation in Flag Leaf Chlorophyll in Spring Wheat Under Mediterranean Conditions

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Plants induce systematic resistant against different types of pathogens by the process of mobilization and solubilization of phosphate (Idris et al, 2004;Erturk et al, 2010). In some studies, it is reported that Bacillus subtilis bacteria enhance the root and shoot length of plant, number of grains and size of the grains, fresh and dry weight, flag leaf area and chlorophyll contents of the treated plants (Waheed et al, 2014;Aboud et al, 2014;Barutcular et al, 2015). Similarly, Trichoderma sp.…”
Section: Introductionmentioning
confidence: 99%
“…Plants induce systematic resistant against different types of pathogens by the process of mobilization and solubilization of phosphate (Idris et al, 2004;Erturk et al, 2010). In some studies, it is reported that Bacillus subtilis bacteria enhance the root and shoot length of plant, number of grains and size of the grains, fresh and dry weight, flag leaf area and chlorophyll contents of the treated plants (Waheed et al, 2014;Aboud et al, 2014;Barutcular et al, 2015). Similarly, Trichoderma sp.…”
Section: Introductionmentioning
confidence: 99%
“…Modern measurement techniques are useful in determination of needs of cultivated crops, including wheat, in respect of top-dressing. They allow for an easy, quick and non-invasive assessment of the plantation condition, including, among others, the indices: Leaf Area Index -LAI (Olsen and Weiner, 2007;Zheng and Moskal, 2009), Mean Tip Angle -MTA (Bobrecka-Jamro et al, 2015) and Soil Plant Analysis Development, SPAD (Hamblin et al, 2014;Barutçular et al, 2015). Analysis of the mentioned indices also allows for predicting a cereal grain yield.…”
Section: Introductionmentioning
confidence: 99%
“…In fully unfold leaves, cell expansion was continued, and photosynthesis structure was establishing. Therefore, if water deficit occur, nitrogen could not be transport to this leaf for chlorophyll synthesis which can be measure as leaf greenness (Barutcular, Toptas, Turkten, Yildirim, & Koc, 2015). Unay & Simsek (2020) had studied heritability of chlorophyll concentration (SPAD) and chlorophyll content index (CCI) in wheat both under waterlogging and control condition.…”
Section: Resultsmentioning
confidence: 99%